The Role of Cash, Receivables, and Inventory Turnover in Driving Profitability in Food and Beverage Manufacturing Firms - Musliha Shaleh; Hukma Ratu Purnama; Rina Rina; Fitriani Fitriani (Owner : Riset dan Jurnal Akuntansi, 2026)
This study investigates the effect of cash turnover, receivables turnover, and inventory turnover on the profitability of food and beverage manufacturing companies listed on the Indonesia Stock Exchange during 2021–2023. The research aims to evaluate how working capital efficiency contributes to firms’ financial performance in a sector characterized by rapid production cycles and high inventory mobility. A quantitative approach was employed using purposive sampling, resulting in 36 firm-year observations. Descriptive statistics, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination were applied to analyze the relationships among variables. The results show substantial variation in working capital indicators and profitability across firms. Cash turnover demonstrates no significant effect on profitability, reflecting the stability of operational cycles in the industry and the stronger influence of production efficiency and cost management. In contrast, receivables turnover exhibits a significant positive impact, indicating that faster collection enhances liquidity and supports improved earnings. Inventory turnover also shows a significant positive effect, suggesting that efficient inventory management reduces holding costs, enhances sales performance, and strengthens cash flows. The simultaneous analysis confirms that cash turnover, receivables turnover, and inventory turnover collectively influence profitability, highlighting the strategic importance of integrated working capital management. Overall, the findings emphasize that receivables and inventory efficiency are critical drivers of profitability, while cash turnover plays a less direct role. This study contributes to the literature by providing empirical evidence from the Indonesian food and beverage manufacturing subsector and underscores the need for firms to optimize working capital components to sustain financial performance. The results also imply that broader operational and market factors should be considered in future research.